Early Intervention for Preschoolers at Risk for Attention-Deficit/Hyperactivity Disorder: Preschool First Step to Success. (February 2016) - Feil, Edward G.; Small, Jason W.; Seeley, John R.; Walker, Hill M.; Golly, Annemieke; Frey, Andy; Forness, Steven R.
This study evaluated the efficacy of the Preschool First Step (PFS) to Success early intervention for children at risk for attention deficit hyperactivity disorder (ADHD). PFS is a targeted intervention for children 3–5 years old with externalizing behavior problems and addresses secondary prevention goals and objectives. As part of a larger multisite, randomized controlled trial, the efficacy of the PFS program was evaluated on a subsample of 45 children who also had elevated comorbid ADHD symptoms as rated by parents and teachers. The PFS program was found to produce significantly higher social skills, and significantly fewer behavior problems across a variety of teacher-and parent-reported measures at postintervention. Effect sizes for teacher-reported effects were large across a variety of social competency indicators, including those specific to ADHD. Effect sizes for parent-reported social skills and problem behaviors were medium. Although not specifically designed for preschoolers at risk for comorbid ADHD, this generic behavioral intervention appeared to be successful for this population. Implications and limitations of the study are discussed.